Effects of NH4+/citrate complexing agent ratio on Ni–Mo and Ni–Mo–O electrodeposits from ammonium citrate baths - To, Dung T.; Park, Sun Hwa; Kim, Min Joong; Cho, Hyun-Seok; Myung, Nosang V. (Frontiers in Chemistry, 2022)
To understand the effect of complexing agents (i.e., ammonium and citrate) in nickel-molybdenum electrodeposition, we calculated the concentration of various Ni and Mo species as a function of pH and initial concentration of metal ions and complexing agents. Additionally, linear sweep voltammetry was systematically investigated to understand their effects on electrodeposition. Furthermore, Hull cell experiments were conducted to understand the effect of ammonium-to-citrate ratio to film compositions and morphology. The results indicated that Ni(NH3)32+ played a critical role in induced co-deposition mechanism of Ni-Mo alloys which involved the reduced Ni and absorbed H atoms. Microstructure analysis of deposits indicated that they transition from smooth laminarly grown amorphous Ni-Mo-O composites to columnar metallic Ni-Mo alloys with globular structure as the ammonium-to-citrate molar ratio increases. The highest Mo content of alloys was as high as 19 at%, and up to 70 at% O was present in the composites.